2009
DOI: 10.1016/j.jbiomech.2009.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and stability of muscle activations during walking in healthy young and older adults

Abstract: To facilitate stable walking, humans must generate appropriate motor patterns and effective corrective responses to perturbations. Yet most EMG analyses do not address the continuous nature of muscle activation dynamics over multiple strides. We compared muscle activation dynamics in young and older adults by defining a multivariate state space for muscle activity. Eighteen healthy older and 17 younger adults walked on a treadmill for 2 trials of 5 minutes each at each of 5 controlled speeds (80 -120% of prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 44 publications
6
72
2
1
Order By: Relevance
“…Another problem is how to perturb the state variables piece by piece. The first problem is usually solved by taking the mean of the trajectory crossings at a Poincaré section of a steady-state walking trial as an approximation of the fixed point [27,30,34,42,43,56,62,68,69,72,74,75,83,92,99,100], which is a reasonable assumption given that steady-state human walking has some degree of stability (i.e. humans can walk without falling every other step).…”
Section: The Maximum Floquet Multiplier 2131 General Descriptionmentioning
confidence: 99%
“…Another problem is how to perturb the state variables piece by piece. The first problem is usually solved by taking the mean of the trajectory crossings at a Poincaré section of a steady-state walking trial as an approximation of the fixed point [27,30,34,42,43,56,62,68,69,72,74,75,83,92,99,100], which is a reasonable assumption given that steady-state human walking has some degree of stability (i.e. humans can walk without falling every other step).…”
Section: The Maximum Floquet Multiplier 2131 General Descriptionmentioning
confidence: 99%
“…The underlying factors contributing to changes in walking performance in the aging population is unclear, but may include changes in muscle strength, balance, joint mobility and cardiovascular fitness [2,6,[11][12][13][14][15][16]. In-depth gait studies in the elderly suggest some factors underlying these gross changes in walking performance include decreases in joint ranges of motion [17], an increased reliance on hip musculature for power generation, and a reduction in the ankle joint moments and powers [4,7,[18][19][20] compared to healthy young control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies [1, 13,14] have suggested that sEMG can reflect local muscle fatigue, as supported by the data in Ta- 90 …”
Section: Evaluation Model For Fatigue Based On Semg Activitymentioning
confidence: 69%
“…Many studies [7,12,13] have investigated muscle fatigue using mean power frequency (MPF), median frequency (MF) and root mean square (RMS) of sEMG. MF and RMS decrease continuously during muscle fatigue, and MPF, MF and RMS can be used to characterize the physiological indicators of muscle charge.…”
mentioning
confidence: 99%